A New Technique for Closed Reduction of Traumatic Posterior Dislocations of the Hip: The 'PGI Technique'. Issue 4 (July 2014) - Sharma, Siddhartha; Kumar, Vishal; Dhillon, Mandeep S.
Many techniques have been described for closed reduction of posterior hip dislocations, but most require forceful and sustained traction, assistants to stabilise the pelvis and awkward positioning of the surgeon and/or the patient. We describe a new technique of closed reduction that does not need traction-countertraction or special positioning and can be safely and effectively performed by one surgeon. Fifteen patients, mean age 36.4 years, were subjected to reduction. There were five type I, four type II and six type III dislocations; ipsilateral injuries included one knee dislocation with patellar fracture, and two cases of tibia fracture. Closed reduction was achieved in 14 (93.3%) hips, with single attempt successful in 13 cases, while one needed two attempts. One hip could not be reduced due to incarceration of a posterior wall fragment and was managed by open reduction and internal fixation. Our new technique has proved to be a reliable, safe and effective alternative for closed reduction of posterior hip dislocations. It can be carried out by one surgeon, does not need traction and can be especially beneficial in polytrauma patients and also in those patients who have pelvic fractures and ipsilateral lower limb injuries.